Stem cells: Role in medical and dental therapies - Sumit Bhateja (Wolters Kluwer Medknow Publications, 2012)
Recent exciting new discoveries place dental professionals at the forefront of helping their patients benefit from potentially life-saving therapies derived from a patient's own stem cells obtained from deciduous or permanent teeth. The great hope is that suitable stem cells, produced in large quantities through cell culture methods and injected into failing tissues and organs, will produce fresh, replacement cells to take over from lost or damaged ones. This ability to grow and regenerate tissues is the focus of the emerging field of -personalized medicine which uses a patient's own stem cells for biologically compatible therapies and individually tailored treatments. This review focuses on the role of oral physicians in the recovery and use of the stem cell in both dental and medical regenerative therapies.